Upaya Meningkatkan Kemampuan Pemecahan Masalah Matematis Siswa Menggunakan Model Problem Based Learning Di Kelas VIII SMP Negeri 17 Medan - Intan Ramadhani Gultom; Nurhasanah Siregar (Unversitas Muhammadiyah Mataram, 2022)
Abstract: This study aims to improve students' mathematical problem-solving skills through problem-based learning models in class VIII-4 SMP Negeri 17 Medan. This type of research is a classroom action research with the subject of 30 students of class VIII-4 SMP Negeri 17 Medan. Data collection techniques in the form of observation and tests. Based on the results of the diagnostic test, the level of students' mathematical problem solving ability is very low with an average grade of 49.17. After taking action in the first cycle, the level of students' mathematical problem solving ability is moderate with an average value of 69.9. The average value of the teacher's ability 2.75 in the sufficient category. After the implementation of the second cycle of action, the level of students' mathematical problem solving ability was high with an average score of 80.4. The value of the teacher's ability to manage learning 3.15 good category. The value of each problem-solving indicator is the indicator of understanding the problem, the average value of the first cycle 85.83 increasing to 95.41 in the second cycle, indicators planning problem solving the average value of the first cycle 71.11 increased to 88.33 in the second cycle, indicators of solving problems the average value of the first cycle was 64.44 increased to 84.72 in the second cycle, and the indicator re-examined the average value of the first cycle of 57.92 increased to 73.73 in the second cycle. Problem based learning model could improve students' mathematical problem solving abilities in class VIII-4 of SMP Negeri 17 Medan.Abstrak: Penelitian ini bertujuan untuk meningkatkan kemampuan pemecahan masalah matematika siswa melalui model problem based learning di kelas VIII-4 SMP Negeri 17 Medan. Jenis penelitian ini merupakan penelitian tindakan kelas dengan subjek 30 siswa kelas VIII-4 SMP Negeri 17 Medan. Teknik pengumpulan data berupa observasi dan tes. Berdasarkan hasil tes diagnostik tingkat kemampuan pemecahan masalah matematika siswa sangat rendah dengan nilai rata-rata kelas 49,17. Setelah dilakukan tindakan pada siklus I, tingkat kemampuan pemecahan masalah matematika siswa sedang dengan nilai rata-rata 69,9. Nilai rata-rata kemampuan guru adal 2,75 kategori cukup. Setelah pelaksanaan tindakan siklus II, tingkat kemampuan pemecahan masalah matematika siswa tinggi dengan nilai rata-rata 80,4. Nilai kemampuan guru mengelola pembelajaran 3,15 kategori baik. Nilai setiap indikator pemecahan masalah; indikator memahami masalah nilai rata-rata siklus I 85,83 meningkat menjadi 95,41 pada siklus II, indikator merencanakan penyelesaian masalah nilai rata-rata siklus I 71,11 meningkat menjadi 88,33 pada siklus II, indikator menyelesaikan masalah nilai rata-rata siklus I 64,44 meningkat menjadi 84,72 pada siklus II, dan indikator memeriksa kembali rata-rata nilai siklus I 57,92 meningkat menjadi 73,73 pada siklus II. Disimpulkan bahwa model problem based learning dapat meningkatkan kemampuan pemecahan masalah matematika siswa di kelas VIII-4 SMP Negeri 17 Medan.